2012
DOI: 10.17660/actahortic.2012.937.31
|View full text |Cite
|
Sign up to set email alerts
|

Studies on in Vitro Propagation Methods in Cactus Species of the Genera Melocactus, Cereus and Lobivia

Abstract: In vitro propagation methods are frequently used for the conservation of rare cacti and also for the production of plants for commercial purposes. Here we report on the micropropagation by axillary shoot proliferation at the cactus species Melocactus salvadorensis, Lobivia tegeleriana and Cereus jamacaru being important as ornamentals and also as a forage and fruit crop in the case of the latter one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
1
1
1
Order By: Relevance
“…These morphotypes showed a particular development, and their presence in greenhouse's seedlings had not been detected previously. The appearance of different morphological shoot types in cacti grown under in vitro conditions have been also reported by other authors [13,[68][69][70], and it is relatively frequent. Although the exact mechanism is still unknown, it seems that the epigenetic factors responsible for regulating gene expression could be behind the appearance of these morphological variants [71].…”
Section: Descriptions Of Morphotypessupporting
confidence: 75%
“…These morphotypes showed a particular development, and their presence in greenhouse's seedlings had not been detected previously. The appearance of different morphological shoot types in cacti grown under in vitro conditions have been also reported by other authors [13,[68][69][70], and it is relatively frequent. Although the exact mechanism is still unknown, it seems that the epigenetic factors responsible for regulating gene expression could be behind the appearance of these morphological variants [71].…”
Section: Descriptions Of Morphotypessupporting
confidence: 75%
“…This research showed that even in the absence of hormones, the shoot could stretch to its maximum length. Even at high BAP concentrations, vitrification could not be seen on axillary shoots (Monostori, Tanács, & Mile, 2010). However, this research found that a greater concentration of BAP may enhance shoot elongation more than a lower concentration of BAP.…”
Section: Effect Different Plant Pgrs On Shoot Lengthcontrasting
confidence: 57%
“…The reduction in salt concentration, more precisely ammonium (NH 4 )/nitrate (NO 3 ) ratio, is also effective to decrease shoot hyperhydricity in T. mombergeri , and a similar finding was also reported in Cereus jamacaru . For instance, vitrified and abnormal shoots of C. jamacaru recovered with the reduction in basal salt, vitamins, and sugar concentrations (Monostori et al, 2010 ). The increase in calcium amount (double-dose) also prevented the hyperhydration of regenerated shoots (Santos-Díaz et al, 2022 ).…”
Section: Constraints Of In Vitro Propagation In Cactimentioning
confidence: 99%